Can green credit policy improve the overseas investment efficiency of enterprises in China?. (15th March 2022) - Zhang, Jijian; Luo, Yichan; Ding, Xuhui
Abstract: Nowadays, countries around the world are increasingly emphasizing the green concept in their foreign investment cooperation. As an important means to guide the green development of China's economy, green credit policy may affect the overseas investment decisions of Chinese enterprises and ultimately affect the investment efficiency. Based on the overseas direct investment data of Chinese A-share listed companies from 2007 to 2019, this paper calculates the overseas investment efficiency at the enterprise level by expanded Richardson model, and further tests the influence of green credit policy on the overseas investment efficiency of Chinese enterprises. The results show that green credit policy can improve the efficiency of enterprises' overseas investment, especially for state-owned enterprises and enterprises in low environmental regulations areas. Therefore, China's financial institutions should strengthen the implementation of green credit policies and formulate differentiated credit schemes for enterprises with different characteristics under the supervision of relevant departments. The results of this paper verify the effectiveness of the green credit policy, which is very important for accelerating the green development of China's overseas investment.